Multi-choice goal programming model for the optimal location of renewable energy facilities. (January 2015) - Chang, Ching-Ter
Abstract: This paper proposes a multi-choice goal programming model for dealing with the capacity expansion planning problem of the renewable energy industry. This model involves decisions regarding the optimal mix of different plant types, location selection and other criteria. Different types of plants should be located in appropriate places so as to minimize the total deviations from predefined goals concerning power generated, investment cost, emission avoided, jobs created, operation and maintenance costs, distance security, and social acceptance. The proposed method is superior to the goal programming model proposed by Ramón and Cristóbal, in that it can avoid underestimation of aspiration level, expand the potential feasible region, and achieve findings more closely approach actual conditions. In addition, the social acceptance of the renewable energy planning problem in Taiwan is modeled by the MCGP to demonstrate its usefulness.